2021
DOI: 10.1002/ams2.626
|View full text |Cite
|
Sign up to set email alerts
|

Medicine at mass gatherings: current progress of preparedness of emergency medical services and disaster medical response during 2020 Tokyo Olympic and Paralympic Games from the perspective of the Academic Consortium (AC2020)

Abstract: Mass gatherings are events characterized by "the concentration of people at a specific location for a specific purpose over a set period of time that have the potential to strain the planning and response resources of the host country or community." Previous reports showed that, as a result of the concentration of people in the limited area, injury and illness occurred due to several factors. The response plan should aim to provide timely medical care to the patients and to reduce the burden on emergency hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Due to the COVID-19 epidemic, a significant amount of challenging work has been done on epidemic prevention and safety [ 5 ]. First, the spread of the Delta and Omicron strains brought about uncertainty in that the Delta and Omicron variant are more contagious than the original strain [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the COVID-19 epidemic, a significant amount of challenging work has been done on epidemic prevention and safety [ 5 ]. First, the spread of the Delta and Omicron strains brought about uncertainty in that the Delta and Omicron variant are more contagious than the original strain [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, our results showed that by carefully enacting proactive measures for mass gatherings, the provision of EMC can remain effective. As of April 2021, the preparation of EMS and disaster medical response system for the 2020 Tokyo Olympic and Paralympic Games (due to start 23 July, 2021) has been steadily underway, 11 and our results suggested that careful measures, like those implemented for the G20 Osaka Summit, would help maintain the EMS system during mass gatherings such as the Olympics.…”
Section: Discussionmentioning
confidence: 79%
“…The rapid global spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic since its first discovery in November 2019 in Wuhan, China, exposed the inadequacies of all global public health systems. The WHO published interim guidelines for the planning for MGs at the time of the current COVID-19 pandemic [9] as well as the publication of recommendations to deal with MG events [10 ▪▪ ,11 ▪▪ ]. Widespread lockdown measures including travel restrictions to limit epidemic spread led to postponement or cancellation of large MG events [12 ▪ ].…”
Section: Respiratory Pathogens In Hajj Pilgrimsmentioning
confidence: 99%